2010
DOI: 10.3109/00016340903294272
|View full text |Cite
|
Sign up to set email alerts
|

Does low molecular weight heparin shorten term labor?

Abstract: Dalteparin, a low molecular weight heparin (LMWH), is given to pregnant women with thrombotic disorders. Clinical observations together with the documented changes of heparan sulfate proteoglycans in normal and protracted labor fostered the idea that LMWH shortens delivery time. Labor time was retrospectively determined among nulliparous pregnant women treated with dalteparin because of previous venous thromboembolism (VTE), thrombophilia or acute VTE during current pregnancy. Their labor time was compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…Our findings may imply a role of LMWH on duration and initiation of labour Similar as those reported by Ekman and coworkers [10]. They also report in a laboratory setting that LMWH stimulates myometrial contractility and cervical remodeling in vitro [14].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our findings may imply a role of LMWH on duration and initiation of labour Similar as those reported by Ekman and coworkers [10]. They also report in a laboratory setting that LMWH stimulates myometrial contractility and cervical remodeling in vitro [14].…”
Section: Discussionsupporting
confidence: 73%
“…Recently, primaparous women treated with LMWH have been reported to have 30% shorter time in labour [10]. In this study we aimed assess if this was true in our pregnant population.…”
Section: Introductionmentioning
confidence: 87%
“…This chemical modification nearly eliminates the anticoagulation activity while preserving the other activities of the sulfated glycan. [31] Tafoxiparin has subsequently advanced into clinical studies and is currently being tested into Phase 2 clinical studies in pregnant women with slow progressing labor or labor arrest (NCT00710242, NCT03001193). [30] These mechanisms are relevant for labor arrest, which can lead to emergency caesarian section.…”
Section: Dilaformentioning
confidence: 99%
“…Prior clinical evidence showed that women who were being treated with low molecular weight heparin, dalteparin, had shorter labor time, thus motivating further investigation for a non-anticoagulating heparin alternative. [31] Tafoxiparin has subsequently advanced into clinical studies and is currently being tested into Phase 2 clinical studies in pregnant women with slow progressing labor or labor arrest (NCT00710242, NCT03001193). In a separate indication of endothelial/epithelial leak, tafoxiparin was tested in two pediatric patients with Gorham-Stout syndrome, where humanitarian approval was granted given the dire condition of the patients.…”
Section: Dilaformentioning
confidence: 99%
“…Purified heparin, where the large molecular weight forms have been removed, are collectively termed low molecular weight heparin (LMWH). 11 In this review, we will discuss recent developments in the use of heparin directed at the prevention of pregnancy complications associated with placental disease, and discuss the non-anticoagulant actions of heparin that have important implications for future research and clinical practice. However, the efficacy and safety of 1/day vs 2/day dosing regimens remains controversial, especially in patients at high-risk of venous thromboembolism.…”
Section: Introductionmentioning
confidence: 99%